1954
DOI: 10.1017/s0021859600046311
|View full text |Cite
|
Sign up to set email alerts
|

Semen characteristics and fertility in the bull

Abstract: 1. Certain characteristics of bull semen have been examined at four artificial insemination centres in England. One hundred and twenty-one samples of semen, comprising 168 ejaculates from seventysix bulls of seven breeds, were examined. The semen from 119 tested samples was subsequently used to inseminate 4604 cows.The following semen characteristics were studied: volume of ejaculate; concentration of spermatozoa; incidence of dead spermatozoa; incidence of morphologically abnormal spermatozoa; initial fructos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

1957
1957
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(32 citation statements)
references
References 35 publications
1
30
1
Order By: Relevance
“…In turn, this quality is correlated with their fertilizing capacity Herman 1941, 1944;Bishop et a!., 1954). While no similar observations were made in the present study, it is not inconceivable that the environment 3 spermatozoa, because of its impaired oxidative activity, had a shorter functional life span both in vitro and in the oviduct.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In turn, this quality is correlated with their fertilizing capacity Herman 1941, 1944;Bishop et a!., 1954). While no similar observations were made in the present study, it is not inconceivable that the environment 3 spermatozoa, because of its impaired oxidative activity, had a shorter functional life span both in vitro and in the oviduct.…”
Section: Resultssupporting
confidence: 73%
“…In fact, the latter investigators reported a negative correlation between sperm respiration and semen fertilizing capacity. Bishop et al (1954) concluded that most of the variation in the oxygen uptake by bull semen can be accounted for by sperm concentration and abnormal spermatozoa.…”
mentioning
confidence: 99%
“…Spermatozoa were released from the epididymides from each male in 0.5 mL bicarbonatebuffered HTF under oil using puncture with a 26-gauge needle and slight pressure and allowed to disperse for 20 min. The spermatozoa were then counted and their motility assessed in a haemocytometer and the live : dead ratio determined after staining with nigrosin and eosin (Bishop et al 1954). The spermatozoa suspensions were diluted so that each contained 1-2 million motile spermatozoa per mL, and droplets of 50 µL were placed in a 35-mm dish, overlaid with 2 mL paraffin oil and put in an incubator at 37 • C in an atmosphere of 5% CO 2 : 95% air.…”
Section: In Vitro Fertilisation Using Spermatozoa From Heated Malesmentioning
confidence: 99%
“…I n addition, this range was chosen because spontaneous p H changes in semen occur within these limits. Semen metabolism and motility have been intensively studied in view of their correlation with semen fertilizing capacity (Bishop et al 1954;Freund & Peterson 1976;Linford et al 1976). Our findings show that sperm collective motility driven by mitochondrial respiration was influenced by the pH of the medium.…”
Section: Discussionmentioning
confidence: 99%